Integrated Multiorgan Bedside Ultrasound for the Diagnosis and Management of Sepsis and Septic Shock - Sweeney, Daniel A.; Wiley, Brandon M. (Seminars in Respiratory and Critical Care Medicine, 2021)
Despite decades of research, the mortality rate of sepsis and septic shock remains unacceptably high. Delays in diagnosis, identification of an infectious source, and the challenge of providing patient-tailored resuscitation measures routinely result in suboptimal patient outcomes. Bedside ultrasound improves a clinician's ability to both diagnose and manage the patient with sepsis. Indeed, multiple point-of-care ultrasound (POCUS) protocols have been developed to evaluate and treat various subsets of critically ill patients. These protocols mostly target patients with undifferentiated shock and have been shown to improve clinical outcomes. Other studies have shown that POCUS can improve a clinician's ability to identify a source of infection. Once a diagnosis of septic shock has been made, serial POCUS exams can be used to continuously guide resuscitative efforts. In this review, we advocate that the patient with suspected sepsis or septic shock undergo a comprehensive POCUS exam in which sonographic information across organ systems is synthesized and used in conjunction with traditional data gleaned from the patient's history, physical exam, and laboratory studies. This harmonization of information will hasten an accurate diagnosis and assist with hemodynamic management.
Keywords: POCUS; bedside ultrasound; sepsis; septic shock